An efficacious dynamic mathematical modelling approach for creation of best collaborative groups. Issue 1 (2nd January 2016) - Kardan, Ahmad A.; Sadeghi, Hamid
Abstract : In many disciplines, including business, publishing, management, health, sports, arts and education, there is a population of people which should be optimally divided into multiple groups based on certain attributes to collaboratively perform a particular task. The problem becomes more complex when some other requirements are also added. They might be importance degrees of grouping criteria, homogeneity, heterogeneity or a mixture of teams, amount of consideration to the preferences of individuals, variability or invariability of group size, having moderators, aggregation or distribution of persons, overlapping level of teams, and so forth. Several researchers have addressed the problem, but they suffered from failure to satisfy all the requirements and/or developed inexact solutions and/or had very long process times. This work reveals how these problems can be mathematically formulated through a binary integer programming approach to construct an effective model which is solvable by exact methods in an acceptable time. The suggested model was validated through data obtained from collaboration of a set of learners in an online learning discussion forum grouped by means of the provided method. The achieved outcomes confirmed that the new approach is satisfactory and promising.